Mix proportion design and carbon emission assessment of high strength geopolymer concrete based on ternary solid waste - Mo Liu; Wenting Dai; Weidong Jin; Mingrui Li; Xue Yang; Yongming Han; Mingxing Huang (Scientific Reports)
Abstract To achieve dual optimization of the mechanical properties and environmental impacts of geopolymer concrete (GPC), this study proposes a high-strength geopolymer concrete (HSGPC) without coarse aggregate. The mix proportion of HSGPC was optimized using the response surface methodology, targeting compressive strength and splitting tensile strength to determine the optimal mix. Additionally, the carbon emission impact of HSGPC was assessed and compared with ordinary Portland cement concrete, ultra-high-performance concrete, and reactive powder concrete. The results indicate that the optimal mix proportion for HSGPC includes 15% fly ash content, 10.30% silica fume content, alkali activator ratio of 2.5, and a NaOH molar concentration of 10 M. Simultaneously, the carbon emissions of HSGPC are reduced by about 30% compared to ordinary Portland cement concrete. Compared to ultra-high-performance concrete and reactive powder concrete of the same strength, the production of HSGPC respectively reduces carbon emissions by 59.87% and 68.24%. This study not only provides valuable technical support for the practical application of GPC in engineering but also holds significant implications for promoting sustainable development in the construction industry.